(3GdeGdjI GdOhdjI Hjf GdSjGSGJ hGdfXe GdeNJdaIs - (3SejI(B, (3RjQGQs ((3GdLRGFQ(B:s (3GdfTQ GdLGeYj GdLOjO(B,s, 2020)
(3jTQM GdcJGH GdeHGOF GdCSGSjI aj GdeGdjI GdOhdjI, MjK jSJJgd HJWhQ GdfXGe GdfbOj GdOhdj bHd hHYO eDJeQ (BBretton woods(3, hCge GdeDSSGJ GdOGYeI dg, ceG jJWQb Edi TQM SYQ GdUQa hCge GdfXQjGJ GdeMOOI dg, Edi LGfH JMdjd echfGJ hYfGUQ ejRGf GdeOahYGJ hJhVjM GdYdGbI GdQGHWI Hjf SYQ GdUQa hejRGf GdeOahYGJ cCge GdCQcGf GdCSGSjI aj GdeGdjI GdOhdjI(B. (3jSYi GdcJGH CjVG Gdi TQM fehPL GdJhGRf GdGbJUGOj Gdcdj d ` (BMundell Fleming (3, GdPj jHjf cjajI JWHjb GdSjGSGJ GdGbJUGOjI aj Vd GNJdGa CfXeI GdUQa, aj GdCNjQ jJe OQGSI GdhMOI GdfbOjI GdChQhHjI heYGdLI bVjI NQhL GHQjWGfjG efgG(B. s
(3GdeQGLY U(B.161s
Keywords: (3CSYGQ GdUQas; (3GdeGdjI GdOhdjIs; (3GdefXeI GdYGdejI ddJLGQIs; (3GdfXGe GdfbOj GdOhdjs